Quality of Adult Chest Radiographs Using Slit Beam Radiography (LODOX) in the Trauma Setting - Du Toit, Maria Johanna (My University, 2014)
LODOX Statscan images the entire body in 13 seconds. There is no information available regarding quality assurance (QA) of this diagnostic imaging modality. We performed QA of the chest component of LODOX images at one Emergency Unit. AIM: To determine and score the prevalence and type of radiographic error of LODOX chest radiographs in the adult trauma setting. To develop a poster as visual aid to illustrate the advantages and disadvantages of the LODOX Stat scan and suggest methods to reduce errors that may influence the diagnostic quality of the image. METHOD: A retrospective descriptive study on one hundred LODOX studies in adults (> 18 years of age) over a period of six weeks was done. The open source OSIRIX software was used to view DICOM files and QA evaluations were performed by three observers, using a pre--‐drafted tick--‐sheet and scoring system. RESULTS: No perfect scores were achieved in our study with an average score of 3.79 out of a possible worst score of 10. The majority of points were scored due to positioning errors and poor planning such as un--‐removed clothing and other artefacts. Radiographic density, contrast and sharpness generally were of good quality contributing less to QA scores. CONCLUSION: Operator dependent errors were the most frequently encountered in LODOX chest images. These were acquired without a trained radiographer in a trauma setting which possess its own challenges. There appears to be a leniency with regards to the quality of the images in this setting. The majority of the images were considered diagnostic, but many of the errors encountered are correctible through proper radiographic principles and this should be targeted when training staff.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Diagnostic Radiology Johannesburg
Keywords: Thorax; Diagnostic Imaging; Emergency Service, Hospital